The Diana project: a legacy for research on gender in entrepreneurship. Issue 1 (31st January 2020) - Brush, Candida G.; Greene, Patricia G.; Welter, Friederike
Abstract : Purpose: The purpose of this paper is to provide a brief history of the evolution of the Diana Project and the Diana International Research Conference. The authors examine the impact of the publications, conferences and research contributions and consider key factors in the success of this collaborative research organization. They discuss the ongoing legacy, suggesting ways to extend this into the future. Design/methodology/approach: This paper uses an historical narrative and a citation analysis. Findings: The Diana Project was founded by five women professors in 1999 with the purpose of investigating women's access to growth capital. Following a series of academic articles, and numerous presentations, the first Diana International Conference was held in Stockholm, Sweden. At this convening, 20 scholars from 13 countries shared their knowledge of women's entrepreneurship, venture creation and growth, culminating in the first volume of the Diana Book Series. Since then, 14 international conferences have been held, resulting in 10 special issues of top academic journals and 11 books. More than 600 scholars have attended or participated in Diana conferences or publications. Research limitations/implications: Contributions from the Diana International Conferences' special issues of journals and books have advanced theory across topics, levels, geographies and methods. Articles emerging from Diana scholars are some of the top contributions about women's entrepreneurship and gender to the field of entrepreneurship. Future research directions are included. Practical implications: This analysis demonstrates the success of a unique woman-focused collaborative research initiative and identifies key success factors, suggesting how these might be expanded in the future. Social implications: To date, more than 600 scholars have participated in the Diana International Conferences or publications. Diana is the only community dedicated to rigorous and relevant research about gender and women's entrepreneurship. Going forward, efforts to expand work on education for women's entrepreneurship, women entrepreneurship faculty and careers, and women entrepreneurs, gender and policy will take place to extend this legacy. Originality/value: The paper is unique in that it is the first to show the substantial legacy and impact of the Diana project since its inception in 1999. Further, it demonstrates how a feminist approach to entrepreneurial principles can yield insights about this unique research initiative and collaborative organization.